2018
DOI: 10.1016/j.euroecorev.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination as favoritism: The private benefits and social costs of in-group favoritism in an experimental labor market

Abstract: In this paper, we examine labor market favoritism in a unique laboratory experiment design that can shed light on both the private benefits and spillover costs of employer favoritism (or discrimination). Group identity is induced on subjects such that each laboratory « society » consists of eight individuals each belonging to one of two different identity groups. In some treatments randomly assigned employer-subjects give preference rankings of potential worker-subjects who would make effort choices that impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 71 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…However, if workers always send the same message, then messages are uninformative of the worker's ability, and the employer's expected earnings from 6 A commonly-used approach is to ask participants for their preference over paintings by Klee and Kandinsky and then assign them to groups according to their stated tastes (e.g., Chen and Li, 2009;Gioia, 2017;Kranton and Sanders, 2017). Others have used preferences over movie genres (Dickinson et al, 2018), colors (Charness et al, 2007), and poetry (Kranton and Sanders, 2017). not hiring (i.e., e7) exceeds her payoff from hiring (i.e., 1 2 × 5 × e12 = e5).…”
Section: Conjecturesmentioning
confidence: 99%
“…However, if workers always send the same message, then messages are uninformative of the worker's ability, and the employer's expected earnings from 6 A commonly-used approach is to ask participants for their preference over paintings by Klee and Kandinsky and then assign them to groups according to their stated tastes (e.g., Chen and Li, 2009;Gioia, 2017;Kranton and Sanders, 2017). Others have used preferences over movie genres (Dickinson et al, 2018), colors (Charness et al, 2007), and poetry (Kranton and Sanders, 2017). not hiring (i.e., e7) exceeds her payoff from hiring (i.e., 1 2 × 5 × e12 = e5).…”
Section: Conjecturesmentioning
confidence: 99%
“…A large number of social psychology studies reported the in-group bias or intergroup discrimination respectively from different aspects, such as, developmental and evolutionary views (Brewer, 1979; Struch and Schwartz, 1989; Van Bavel et al, 2008; Yang et al, 2014; Oestereich et al, 2019). Such in-group bias or out-group discrimination modulates various people’s social behaviors, including both helpful and harmful behaviors (Cikara et al, 2011, 2014; Dickinson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of labor negotiation outcomes may even extend beyond the firm if those not hired harbor resentment that leads to antisocial behaviors. Such impacts represent difficult-to-measure spillover effects of labor negotiations, but recent experiments suggest such effects exist (Dickinson et al 2018).…”
Section: Fairness In Negotiationsmentioning
confidence: 99%